An Experimental Study on the Comparison of Learning Outcomes in VLAN Configuration Using Graphical Network Simulator 3 and Cisco Packet Tracer - Puspanda Hatta; Ifan Fadhlur Ramadhan; Agus Efendi (Journal of Informatics and Vocational Education, 2025)
Selecting an appropriate network simulator for advanced VLAN instruction in higher education remains an unresolved pedagogical challenge, as empirical comparisons of GNS3 and Cisco Packet Tracer at university level are scarce. This study aimed to examine (1) whether a significant difference in VLAN configuration learning outcomes exists between students using GNS3 and those using Cisco Packet Tracer, and (2) the relative effectiveness of each simulator for students of the Informatics and Computer Engineering Education Program (PTIK) at Universitas Sebelas Maret. A quasi-experimental pre-test–post-test design was employed with two intact classes (N = 30) from the 2023 cohort, randomly assigned to the GNS3 condition (n = 15) and the Cisco Packet Tracer condition (n = 15). Learning outcomes were measured using ten validated essay items (α = 0.673) and analysed via an independent-samples t-test and normalised gain (N-gain) index. Results revealed that GNS3 users outperformed Packet Tracer users on the post-test (mean 79.33 vs. 72.80), with a statistically significant difference (t (28) = 2.224, p = 0.034). N-gain analysis further showed that the GNS3 group achieved moderate learning effectiveness (g = 0.452), compared to the low category recorded for the Cisco Packet Tracer group (g = 0.277). These findings suggest that GNS3’s authentic Cisco IOS emulation fosters deeper cognitive engagement with advanced VLAN tasks—including inter-VLAN routing and native CLI syntax—than the abstracted environment of Packet Tracer. GNS3 is therefore recommended as the primary simulator for advanced networking courses in higher education, while Packet Tracer remains appropriate for introductory-level instruction. Future research should replicate this design with larger, multi-institutional samples to strengthen external validity.